Regulation of the EGFR Pathway by HSP90 Is Involved in the Pathogenesis of Cushing’s Disease - Shen, Yue; Ji, Chenxing; Jian, Xuemin; Zhou, Juan; Zhang, Qilin; Qiao, Nidan; Zhang, Yichao; Shou, Xuefei; Zhou, Xiang; Ma, Zengyi (Frontiers in Endocrinology, 2021)
Purpose: To investigate the role of heat-shock protein Hsp90 in adrenocorticotropic hormone (ACTH)-secreting cells, and to explore the potential clinical application of an inhibitor of Hsp90, 17-N-allylamino-17-demethoxygeldanamycin(17-AAG) in corticotropinomas (also known as “Cushing’s disease” (CD)). Methods: Culture of mouse pituitary tumor (AtT-20/D16v-F2 (ATCC® CRL-1795™)) cells and human pituitary ACTH-secreting tumor cells were employed. Hepatocellular carcinoma cell line (HLE) was used to evaluate EGFR inhibition by 17-AAG. Cell viability was evaluated using a commercial kit. The ACTH level was measured by a radioimmunoassay. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) was used to measure expression of proopiomelanocortin (POMC) mRNA. Western blotting was done to measure protein levels. Results: 17-AAG suppressed the viability and proliferation, and promoted the apoptosis, of AtT-20/D16v-F2 cells. 17-AAG suppressed the synthesis and secretion of ACTH in AtT-20/D16v-F2 cells and down-regulated POMC transcription. 17-AAG acted in a similar pattern upon treatment with human pituitary ACTH-secreting tumor cells. Inhibition by 17-AAG was stronger in human pituitary ACTH-secreting tumor cells carrying the ubiquitin-specific protease-8 (USP8) mutant in comparison with cells carrying wild-type USP8. Conclusions: The HSP90 inhibitor 17-AAG reduced the viability and secretory function of human pituitary ACTH-secreting tumor cells, and tumor cells carrying the USP8 mutant were more sensitive to 17-AAG than tumor cells carrying wild-type USP8. 17-AAG could be a potential treatment option for CD.